Household Waste Management with Waste Bank in Stunting Area at Puskesmas Ambacang, Padang City - Mahaza; Sari Arlinda; Suksmerri; Lindawati; Muklis (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Household waste management is an important environmental and public health issue, especially in areas with high stunting rates, where overall community health can be compromised due to poor sanitation practices. This study explores the implementation of a waste bank system in stunting-prone areas in the working area of the Ambacang community health centre in Padang city. Waste banks function as a community-based approach to managing household waste by encouraging residents to separate and store recyclable materials in exchange for financial benefits. It also aims not only to reduce environmental pollution but also to empower local residents economically and improve public health. This service examines the effectiveness of waste banks in changing household waste management behaviour, their contribution to reducing health risks associated with waste mismanagement and their potential to alleviate stunting through improved environmental sanitation. The waste bank model encourages greater community involvement in waste segregation and recycling thus contributing to a cleaner living environment.